Analysis of Clinical Skill Performance During Medical Internship at Department of Surgery, Debre Tabor University, Ethiopia - Hasen, Yalew; Aderajew Mequanint; Tewodros Teshome; Amsalu Belete; Derso Bekele (Sriwijaya Journal of Surgery, 2024)
Introduction: Direct observation of procedural skill (DOPS) is a method of assessing a trainee's performance in a work setting. It involves a supervisor monitoring the trainee while they carry out a procedural skill using a structured checklist. This study aimed to investigate the perceptions and levels of satisfaction among medical interns and their assessors during their surgical clinical attachments at the Department of Surgery, Debre Tabor University, Ethiopia. Methods: The research was based on the steps of an action research project. The test includes basic surgery procedures like securing a peripheral IV line and drawing blood for testing, as well as skills like suturing and knot tying, putting in a nasogastric tube (NGT), and putting in a trans-urethral urinary catheter. The data gathering instruments used were self-administered, semi-structured questionnaires for both interns and their evaluators. After the implementation of the DOPS interventions, the questionnaire was distributed to both students and instructors. The data were analyzed using SPSS version 26.0 software, calculating frequency and percentage values for comparison. Results: Most of participants believe that DOPS has the potential to enhance the objectivity of assessing students' skills. The majority of participants strongly agreed that DOPS enhances the relationship between students and teachers, provides valuable feedback to medical interns, should continue in other departments in the future, and is an effective teaching and learning tool. The DOPS performance showed a significant improvement between the first and second assessments in all four procedures. Conclusion: DOPS can serve as a standard tool for assessing fundamental practical abilities in the surgical fields. Given that action research involves a paradigm shift and necessitates ongoing reflection and improvement, it is advisable to conduct additional studies to evaluate the performance of interns in all other departments.